Transport Properties and Related Thermodynamic Data of Binary Mixtures - Gammon, Bruce E. (American Institute of Chemical Engineers : Design Institute for Physical Property Data)
Contenido: Tablas: Propiedades críticas; Densidad; Coeficiente de difusión; Solubilidad; tensión superficial; Conductividad térmica; Viscosidad; Apéndice.